A study on non-steroidal anti-inflammatory drugs (NSAIDs) that induced cardiovascular adverse effect in Malaysia from 2010 until 2014 - Salim, Liyana (2016)
Non-steroidal anti-inflammatory drugs (NSAIDs) are used to treat pain and inflammation. Some commonly used NSAIDs are ibuprofen, diclofenac, acetylsalicylic acid, mefenamic acid and naproxen. For the past ten years, there were studies done that found NSAIDs can increase the risk for cardiovascular problems. The present study aims to study on the most common NSAIDs that induced cardiovascular adverse effect in Malaysia from the year 2010 until 2014. What is the incidence, the severity and the drug-causal relationship of the cardiovascular adverse effect? Does the extent of severity of the cardiovascular adverse effect was affected by patients' demographic factor, number of concomitant drugs, and drug dose. This is a retrospective study. All NSAIDs induced or associated with cardiovascular adverse effect reported to Malaysian Adverse Drug Reactions Advisory Committee (MADRAC) from 2010 until 2014 were collected. All samples of data were collected from MADRAC at Pharmacovigilance Section, Centre of Post Registration Product and Cosmetic Control, National Pharmaceutical Control Bureau (NPCB), Ministry of Health. A total of 78 cases from 98 cases were finalized and analyzed after they fulfilled the inclusion criteria. 52.6% of the patients were male, 60% Malay and 26.9% were between 46 to 60 years old. For the causality assessments of the reports, 64% were classified as probable (C2) and the extent of severity was moderate (46%). The concomitant drugs used were mild (91 %) where the number of drugs used was not more than three. Statistical analysis found that there were no association between gender (p = 0.152), age (p = 0.338), race (p = 0.592) and number of concomitant drugs (p = 0.407) with extent of severity. Diclofenac was found to be the most common NSAIDs that induced cardiovascular injury with 64.1 %. 62% of cases reported for diclofenac were dose below 75 mg. It was found that drug dose (p = 0.224) was not associated with extent of severity. Diclofenac was found to be the most reported NSAIDs with adverse effects related to cardiovascular.